THE INFLUENCE OF EARLY MARRIAGE ON MONETARY POVERTY IN INDONESIA - Wulansari Dyah Rahayu; Heni Wahyuni (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction/Main Objectives: The aim of this study is to analyze the influence of early marriage on monetary poverty in Indonesia. Background Problems: Recent studies on early marriage show that the prevalence of early marriage in Indonesia reached 13.5 percent (Marshan et al., 2013) and that early marriage exacerbates poverty, which causes an increase in the economic burden on the family (Djamilah, 2014), an increase in family harassment, divorce and individuals not continuing with their schooling (Putranti, 2012), and an increase in the chance of poverty by 31 percent in the United States (Dahl, 2010). However, most studies are qualitative studies. Research Methods: This study uses recent data from the Indonesian Family Life Survey (IFLS), year 2014; with the sample being women who get married for the first time at less than 18 years old as a proxy for early marriage; and monthly per capita income as a measurement of monetary poverty. This study employs a binary method for the binary dependent variable which is whether the women experience monetary poverty. Findings/Results: The result shows that the prevalence of early marriage in Indonesia has reached 16.36 percent. Among those, 46.61 percent of the women who marry in their teens (before 18 years old) do not complete the mandated nine years of basic education, and 52.35 percent of the women who were married at an early age do not have a health insurance card. The results of the binary probit model show that early marriage does not affect the possibility of a woman experiencing monetary poverty. It means that early marriage does not influence the monthly per capita income of the women. Conclusion: The results of this study imply that other measurements of poverty may need to be considered. Therefore, the policies that are aimed at reducing early marriage should consider the impact of other factors on poverty.